The Impact of Information Technology on Tourism Development Strategy - Nama, I Ketut; Pujiharjanto, C. Ambar; Santosa, Budi; Wenerda, Rias (RSF Conference Series: Business, Management and Social Sciences, 2021)
Along with the development of industry 4.0, conventional tourism development strategies have become irrelevant. The evolving information technology demands rapid adjustments in order to survive in the market. The purposes of this study are to analyze internal and external factors of the development of tourist destinations based on the use of information technology, using SWOT analysis and the ordinary least square model. The results of this study indicate various strategies that can be carried out by a tourism destination in order to compete with similar destinations. Another result is that travel behavior, age, and gender can affect the tendency to agree in the tourism development based on the use of information technology. The implication is that changes in information technology must be immediately responded to in order to survive in competition.